Colony Propagation of Bee Trigona Sp. with The Nest Grafting Method on Rizhophora Sp. - Irundu, Daud; Awaluddin (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2021)
Nowadays the need for honey continues to increase, various methods are used to fulfill the needs of honey, including using destructive methods. Cultivation using the Trigona Bee colony graft method can be an alternative to producing honey and other environmentally friendly products. The aim of this research was to determine the colony effectiveness using the grafting method on Rhizophora trees in the mangrove forest of Mirring Village, Binuang District, Polewali Mandar Regency. This research was conducted from January to March 2021. The method used in this research was the colony grafting technique using 9 stup for 30 days followed by observations 30 days after the graft was released by observing the activity of bees and the components of the hive contained in each stup. The results showed that the remaining and active colonies in the stup after the colony grafting process were 5 stup out of 9 stup. The hive component were dominated by propolis, bee-pollen and broot.